2021
DOI: 10.1242/jeb.242846
|View full text |Cite
|
Sign up to set email alerts
|

Diet mediates thermal performance traits: implications for marine ectotherms

Abstract: Thermal acclimation is a key process enabling ectotherms to cope with temperature change. To undergo a successful acclimation response, ectotherms require energy and nutritional building blocks obtained from their diet. However, diet is often overlooked as a factor that can alter acclimation responses. Using a temperate omnivorous fish, opaleye (Girella nigricans), as a model system, we tested the hypotheses that 1) diet can impact the magnitude of thermal acclimation responses and 2) traits vary in their sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
34
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 115 publications
(155 reference statements)
9
34
0
Order By: Relevance
“…This finding suggests that energy mobilization may be a fundamental factor that limits thermal tolerance. Consistent with this idea, improved nutrition has increased the thermal tolerance of redside dace (Turko et al, 2020), and several other studies have demonstrated similar patterns in other species (Hardison et al, 2021;Lee et al, 2016;Robinson et al, 2008). We speculate that there may therefore be negative consequences for the ability of fishes to cope with thermal stress in conjunction with other environmental factors that also increase energy demands (e.g., the metabolic detoxification of pollutants; Du et al, 2018).…”
Section: Conservation Implicationssupporting
confidence: 80%
“…This finding suggests that energy mobilization may be a fundamental factor that limits thermal tolerance. Consistent with this idea, improved nutrition has increased the thermal tolerance of redside dace (Turko et al, 2020), and several other studies have demonstrated similar patterns in other species (Hardison et al, 2021;Lee et al, 2016;Robinson et al, 2008). We speculate that there may therefore be negative consequences for the ability of fishes to cope with thermal stress in conjunction with other environmental factors that also increase energy demands (e.g., the metabolic detoxification of pollutants; Du et al, 2018).…”
Section: Conservation Implicationssupporting
confidence: 80%
“…The supplementation of Ulva spp. to diet of the omnivorous fish opaleye ( Girella nigricans ) reduced their maximum heart rate ( f Hmax ) when compared to fish fed with carnivorous diet without changing their thermal tolerance parameters ( Hardison et al, 2021 ). Here, the aim was to discover if supplement feeding could improve the cardiac performance of the fish during warming.…”
Section: Discussionmentioning
confidence: 99%
“…Another option to enhance the cardiovascular performance of fish at high temperatures could be changing the composition of their feed, as recently shown by Hardison et al (2021) . Functional feeds are enriched diets with natural components derived generally from terrestrial plants and seaweeds with potential benefits in the prevention and treatment of cardiovascular diseases ( Hasler et al, 2000 ; Marriott, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that our most extreme test temperatures (i.e., 13 °C and 19 °C for static) were within the range of temperatures experienced during seasonal thermal variation in their native habitat, and thus may be within the thermal range for which cardiac performance is optimized. Indeed, Hardison et al (2021) found a significant difference in f Hmax between opaleye acclimated to 12 and 20 °C, temperatures which may represent thermal extremes and, at least for 12 °C, be outside the optimal thermal range for cardiac performance. Future work looking to examine the thermal limits of eurythermal fishes may consider exposing fish to temperatures exceeding the mean annual maximum and minimums, and should also consider examining lower levels of biological organization (e.g., thermal acclimation capacity of cardiac ion channels, pacemaker cells, B-adrenoreceptors, or sarcoendoplasmic reticulum Ca 2+− ATPase) to elucidate mechanisms of tolerance ( Castilho et al, 2007 ; da Silva et al, 2011 ; Graham and Farrell, 1989 ; Keen et al, 2017 ; Korajoki and Vornanen, 2013 ; Landeira-Fernandez et al, 2004 ; Shiels et al 2015 ; Shiels et al, 2000 ; Vornanen, 2021 ).…”
Section: Discussionmentioning
confidence: 94%
“…Following a 30 min equilibration period at the acclimation temperature ( Ferreira et al, 2014 ; Hansen et al, 2017) , atropine sulfate (1.2 mg kg −1 in 0.9% NaCl) was injected intraperitonially to block vagal tone. Fifteen minutes later, isoproterenol (4 μg kg −1 in 0.9% NaCl) was also injected intraperitonially to maximally stimulate β-adrenoreceptors ( Hardison et al, 2021 ). Fifteen minutes after isoproterenol injection, water temperature was heated at 1 °C every 6 min using a Polystat recirculating heater/chiller (Cole-Palmer, Vernon Hills, IL, USA).…”
Section: Methodsmentioning
confidence: 99%